2014
DOI: 10.3109/02713683.2014.917190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Injections of Ranibizumab on Retinal Nerve Fiber Layer Thickness in Patients with Age-Related Macular Degeneration

Abstract: Long-term treatment with anti-vascular endothelial growth factor (VEGF) agents did not lead to significant changes in RNFL thickness in a patient population with wet AMD. Chronic therapy with intravitreal anti-VEGF agents does not appear to adversely affect RNFL thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
5
23
1
Order By: Relevance
“…The study with the longest follow-up in the literature analyzed the changes in peripapillary nerve fibers only after a mean 13.8 ± 3.8 IVIs, which corresponds to slightly more than 1 year of monthly IVIs. This study demonstrated no statistically significant difference compared to the initial data [14]. …”
Section: Discussioncontrasting
confidence: 56%
“…The study with the longest follow-up in the literature analyzed the changes in peripapillary nerve fibers only after a mean 13.8 ± 3.8 IVIs, which corresponds to slightly more than 1 year of monthly IVIs. This study demonstrated no statistically significant difference compared to the initial data [14]. …”
Section: Discussioncontrasting
confidence: 56%
“…However, no significant change in RNFL thickness was observed comparing the initial visit to the Month 6 visit and the last follow-up visit in our study. Our result was consistent with previous studies focusing on anti-VEGF-A agents56. The decrease in RNFL thickness with increasing age is approximately 0.26 μm per year; therefore, the effect of a natural decrease in RNFL thickness during the follow-up period was negligible19.…”
Section: Discussionsupporting
confidence: 92%
“…According to the latest meta-analysis, no association was observed between anti-VEGF injections and RNFL thickness changes3. However, those pooled studies mainly focused on ranibizumab (Lucentis; Genentech, Inc., South San Francisco, CA, USA) and bevacizumab (Avastin; Genentech, Inc.)456, which are monoclonal antibodies against VEGF-A7. Information about RNFL changes after other anti-VEGF injections is limited.…”
mentioning
confidence: 99%
“…However, when 2 low-biased, controlled clinical trials were examined separately, repeated anti-VEGF injection was associated with RNFL loss. In comparison to other studies finding no change of RNFL thickness during intravitreal treatment for nAMD, these studies either had a shorter observation time (El-Ashry et al [25] ), a smaller cohort (Demirel et al [15] ), or evaluated RNFL at a different location (Demirel et al [15] ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Demirel et al [15] analyzed global and nasal RNFL thickness with Cirrus OCT in 29 nAMD patients with >10 ranibizumab injections and a mean follow-up of 39 months. This study, like another, found no significant changes of the nasal RNFL [13,15] . A meta-analysis by Shin et al [16] published in April 2016 summarizes the data of 288 eyes in total.…”
Section: Introductionmentioning
confidence: 99%